Optimizing mulch thickness for enhanced vegetative growth of khirni (Manilkara hexandra) (Current Horticulture, 2024)
A field experiment for optimizing mulch thickness for enhanced vegetative growth of khirni (Manilkara hexandra Roxb.) cv. Thar  Rituraj was conducted during the 2019-20 at College of Horticulture and Forestry, Jhalawar, Rajasthan. Among different thicknesses  application of T6-12 cm thickness of dry grass to individual plants was significantly superior to all other treatments, but it was on at  par with T5-10 cm thickness of dry grass. In treatment T6, an increase in shoot and leaf parameters, such as rootstock girth (10.98%),  scion girth (11.05%), plant height (32.61%), number of nodes/shoot (80.52%), number of internodes/shoot (94.33%), number of  leaves/plant (39.94%), leaf length (13.45%) and leaf area index (1.50%), were recorded during February 2020.
Keywords: Development; Growth; Mulching; Thickness; Vegetative growth